MiR‐155 expression in antitumor immunity: The higher the better?. Issue 4 (8th February 2019) - Michaille, Jean‐Jacques; Awad, Hamdy; Fortman, Emily C.; Efanov, Alexander A.; Tili, Esmerina
Abstract: MicroRNAs are small noncoding RNAs that modulate gene expression either directly, by impairing the stability and/or translation of transcripts that contain their specific target sequence, or indirectly through the targeting of transcripts that encode transcription factors, factors implicated in signal transduction pathways, or epigenetic regulators. Abnormal expression of micro‐RNAs has been found in nearly all types of pathologies, including cancers. MiR‐155 has been the first microRNA to be implicated in the regulation of the innate and adaptative immune responses, and its expression is either increased or decreased in a variety of liquid and solid malignancies. In this review, we examine the oncogenic and antitumor potentials of miR‐155, with special emphasize on its dose‐dependent effects. We describe the impact of miR‐155 levels on antitumor activity of lymphocytes and myeloid cells. We discuss miR‐155 dose‐dependent effects in leukemias and analyze results showing that miR‐155 intermediate levels tend to be detrimental, whereas high levels of miR‐155 expression usually prove beneficial. We also examine the beneficial effects of high levels of miR‐155 expression in solid tumors. We discuss the possible causal involvement of miR‐155 in leukemias and dementia in individuals with Down's syndrome. We finally propose that increasing miR‐155 levels in immune cells might increase the efficiency of newly developed cancer immunotherapies, due to miR‐155 ability to target transcripts encoding immune checkpoints such as cytotoxic T lymphocyte antigen‐4 or programmed death‐ligand 1.